Encouraging Pro-Social Behavior Through Ecological Motivation and Self-Esteem - Kuswati, Rini; Krisnawan, Gata (Universitas Airlangga, 2024)
This research examines ecological motivation's influence on pro-social behaviour mediated by self-esteem. This research describes pro-environmental behaviour in purchasing environmentally friendly products that support issues related to the circular economy in the digital era. The research methodology uses a quantitative deductive approach to test hypotheses. The research design used was a survey to determine environmentally friendly purchasing behaviour, with a sample size of 165 respondents from the Surakarta city area and the public. Non-probability sampling was carried out using the purposive sampling method. Instrument testing includes assessing convergent and discriminant validity and reliability testing using Cronbach's alpha and composite reliability to produce valid and reliable results. Instrument and hypothesis testing used SmartPLS 3.2.9 software to produce output for the outer and inner models. Data analysis involved a two-step algorithmic process and bootstrapping. The results of the analysis show that ecological motivation towards environmentally friendly purchases has a significant effect on pro-social behaviour. It has been proven that the intention to purchase environmentally friendly products mediates self-esteem in purchasing behaviour for environmentally friendly products.